Comparative Evaluation of the Diuretic Activity of Infusions of Four Species of the Genus Astragalus (Astragalus L.) in the Experiment - U. A. Matvienko; A. Yu. Karetnikova; N. A. Durnova (Разработка и регистрация лекарственных средств, 2024)
Introduction. Astragalus L. is the largest genus of the Fabaceae family and one of the largest genera of vascular plants on Earth. The official type of raw material included in the 7th edition of the European Pharmacopoeia is Radix Astragali – the dried root of Astragalus membranaceus (Fisch.) Bunge and Astragalus mongholicus Bunge. Extracts obtained from astragalus root have anti-inflammatory, immunostimulatory, antioxidant, diuretic effects. In traditional medicine, the herb of Astragalus dasyanthus Pall. is actively used. An infusion of the herb of Astragali dasyanthi has sedative, hypotensive and diuretic effects. However, the raw material is not official and is not included in the list of plant raw materials of the State Pharmacopoeia of the Russian Federation of the XIV edition. Promising species of the genus Astragalus L. can be not Astragalus membranaceus (Fisch.) Bunge and Astragalus dasyanthus Pall., but also other species, for example, Astragalus varius S.G. Gmel., Astragalus testiculatus Pall., Astragalus henningii (Stev.) Klok., which are widespread in the Saratov region. In view of the available data on the presence of the herb of Astragalus dasyanthus Pall. and Astragalus membranaceus (Fisch.) Bunge of the diuretic effect, it is of interest to study the diuresis of extracts from the herb of other species of the genus Astragalus L.Aim. To study the diuretic activity of infusions from the herb of four types of astragalus: Astragalus dasyanthus, Astragalus varius, Astragalus testiculatus, Astragalus henningii in 4- and 24-hour experiments on male rats.Materials and methods. The study of the diuretic activity of aqueous extracts from the herb of four types of Astragalus was performed on 42 white male rats, which were divided into 6 experimental and control groups of 6 animals. Aqueous extracts from Astragalus herb were prepared in the ratio of raw material-extractant 1:10, all obtained infusions met the requirements for these dosage forms according to the General Pharmacopoeia of the State Fund of the Russian Federation of the XIV edition. Aqueous extracts were administered to animals intragastrically through an umbrella at a dose of 100 mg/kg. During the experiment were collected 4-hour and 24-hour portions of urine. The comparison drug in the 4-hour experiment was furosemide at a dose of 1 mg/kg, and in the 24-hour experiment, hydrochlorothiazide at a dose of 20 mg/kg. Results and discussion. As a result of the experiment, the diuretic effect of the infusion of the herb of Astragalus dasyanthus both in the 4-hour experiment and in the 24-hour experiment. Also in both experiments, the most pronounced diuretic effect was found in the infusion of the herb of Astragalus henningii at a dose of 100 mg/kg compared with herb infusions Astragalus dasyanthus, Astragalus varius. Diuretic effect Astragalus henningii exceeded the diuretic activity of furosemide at a dose of 1 mg/kg, while a comparable effect was observed with hydrochlorothiazide at a dose of 20 mg/kg. Diuretic effect of herbal infusion Astragalus varius in a 4-hour experiment exceeded the diuretic effect of herb infusion Astragalus dasyanthus and furosemide at a dose of 1 mg/kg, and in a 24-hour experiment comparable to the diuretic effect of herb infusion Astragalus dasyanthus, but lower than that of hydrochlorothiazide at a dose of 20 mg/kg and herb infusion Astragalus henningii. Diuretic effect of herbal infusion Astragalus testiculatus at a dose of 100 mg/kg was not detected both in the 4-hour and in the 24-hour period. The diuretic activity of the group that received the infusion of the herb of Astragalus testiculatus was at the level of the control group, compared with other experimental groups, a statistically significant decrease in diuresis was observed in animals.Conclusion. The experiment confirmed the diuretic effect of the infusion of the herb of Astragalus dasyanthus and for the first time discovered the diuretic effect of the infusion of the herb of Astragalus varius and the infusion of the herb of Astragalus henningii. Among the studied infusions, the most pronounced diuretic effect was observed in Astragalus henningii herb infusion. The diuretic effect of Astragalus varius infusion is higher than that of Astragalus dasyanthus infusion. in a 4-hour experiment and did not differ in effectiveness from the infusion of the herb of Astragalus dasyanthus in a 24 hour experiment. The diuretic effect of the infusion of the herb astragalus oviparous was not revealed.